Anti-Saccharomyces cerevisiae Antibodies Are Only Modestly More Common in Subjects Later Developing Crohn's Disease - Bodecker-Zingmark, L.; Widbom, L.; Hultdin, J.; Eriksson, C.; Karling, P. (Digestive diseases and sciences, 2023)
Background The pathogenic processes in the preclinical phase of inflammatory bowel disease (IBD) are mainly unknown. Aims To study typical antibodies for IBD in the preclinical phase in a cohort of Northern Sweden. Methods Antibodies typical for IBD (ASCA, pANCA, lactoferrin-ANCA, antibodies to goblet cells, and pancreas antigen) were analyzed in 123 subjects with preclinical ulcerative colitis (UC), 54 subjects with preclinical Crohn's disease (CD) and in 390 sex- and age-matched controls. In addition, in a subset of subjects, inflammatory markers (CRP, albumin, calprotectin and ferritin) were measured in plasma. Results The mean years between blood samples and IBD diagnosis were for UC 5.1 (SD 3.5) years and CD 5.6 (SD 3.5) years. There was no difference in the proportion of overall positive antibodies between subjects who later developed IBD compared to controls (16.9% vs. 12.3%; p = 0.137). The subjects who later developed CD had a significantly higher proportion of positive ASCA compared to controls (9.3% vs 2.8%; p = 0.034), but for all other antibodies, there were no differences compared to control subjects. Subjects with preclinical IBD and elevated antibodies showed significantly higher plasma calprotectin levels compared to subjects without antibodies (980 μg/L vs 756 μg/L; p = 0.042), but there was no difference in the levels of CRP, albumin and ferritin. Conclusions We found no significant increase in antibodies typical for IBD years before diagnosis except for ASCA, which was slightly more common in subjects who later developed CD. Very few subjects had detectable antibodies to goblet cells and pancreas antigen.